Kriteria penyusunan soal higher order thinking skills dalam pembelajaran matematika (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The change in the current assessment system in Indonesia is the adoption of Higher Order Thinking Skills (HOTS) based assessments. The application of HOTS-based assessment aims to make the learning process, especially mathematics, motivate students to be able to develop creative thinking skills. In this article, it examines conceptually with the aim of providing teachers with the knowledge about the concepts and characteristics of HOTS-based question preparation. Characteristics in making HOTS questions are (1) measuring high-level thinking skills, (2) using problems in daily life, (3) and using various types of questions.
Keywords: HOTS; characteristics; questions; mathematics